Pendampingan Optimalisasi Pemanfaatan Daun Kelor Sebagai Pangan Tambahan di Desa Randuputih - Gustav Ahmadi; Thariq Zinedin Widiansyah; Linc Bellatrix Adhara; Kustini Kustini; Zainal Abidin Achmad; Dita Atasa (Universitas Maritim AMNI Semarang, 2024)
The activity of optimizing the utilization of moringa leaves as an additional food source in Randuputih Village has become a strategic solution to improve the nutritional status of the community, reduce the incidence of stunting, and alleviate hunger in support of achieving Sustainable Development Goal (SDG) 2. This initiative is carried out by students from the Community Service Program (KKNT) Group 1 at UPN